The Effect of Ajwa Date Fruit Extract (Phoenix Dactylifera L.) Against Liver Damage in White Rats (Rattus Norvegicus) Induced by Meloxicam - Fatimah Mappanyompa; Arsyad, M Aryadi; Sari, Dwi Kesuma; Natsir, Sartini; Cangara, Muhammad Husni; Djabir, Yulia Yusrini (Hasanuddin University, 2023)
Abstract Objective: This study was aimed to investigate the protective effect of Ajwa date palm extract (Phoenix Dactylifera L.) against liver damage in white rats (Rattus norvegicus) induced by Meloxicam. Methods: The samples used in this study were twenty five male white rats divided into five groups with body weight 200 – 300gr, namely a healthy control group, negative control given Meloxicam 30mg/kgBB, treatment group 1 was given Ajwa date fruit extract 75mg/kgBW and Meloxicam 30mg/kgBW, treatment group 2 was given Ajwa date fruit extract 150mg/kgBW and Meloxicam 30mg/kgBW, and treatment group 3 was given Ajwa date fruit extract 300mg/kgBW and Meloxicam 30mg/BW for 14 days. On the 15th day, the rats were anesthetized for blood tests and euthanized for liver organ observation. Results: The result showed by giving Ajwa date palm extract with higher doses and Meloxicam 30mg/kgBW, resulted a decrease in ALT and AST enzyme levels which were close to normal values ​​in rats. Histological observation showed extensive damage to liver cell tissue, with signs of inflammation, hemorrhage, necrosis, and hydropic degeneration. By giving high doses of Ajwa date palm extract and Meloxicam 30mg/kgBW, gave a view of a decrease degree on liver tissue damage. Conclusion: The extract of Ajwa date palm (Phoenix Dactylifera L.) can provide a protective effect against liver damage in white rats (Rattus Norvegicus) induced by Meloxicam with decreased levels of liver function enzymes which are Alananine Transaminase (ALT) and Aspartate Aminotransferase (AST), along in the changes of liver histopathological view which showed a decrease degree of liver cell tissue damage. Keywords: Ajwa date palm extract; Meloxicam; Liver tissue damage.